Efek Pembelajaran Napas Dalam Terhadap Toleransi Nyeri Dan Perubahan Tanda-Tanda Vital Perioperatif Appendiktomy Di Recovery Room Lt III Dan Kamar Operasi Lt V IRD RSU Dr. Soetomo Surabaya - Herry Sasongko, - (2006)
Deep breathing relaxation technique is a non-pharmacology method, which fills the basic essence in, decreases pre and post appendictomy operation’s pain. All this time, deep breathing technique to the patient with pre appendictomy has not been admited. This technique also has an influence to vital signs alteration into a normal direction. Deep breathing relaxation can be explained by gate control theory. The purposes of this research were to know the deep breathing learning effectiveness to pain tolerance and vital signs alteration. This research method used pre experimental one group pre-posttest design; its population is appendicsitis patients. Total samples are 30 patients who comply with inclusion criteria using purposive sampling method. Data collection uses questionnaire and observation. Statistical tests use Wilcoxon Signed Rank and Paired t Test with p significance < 0.05. The research results from deep breathing learning to pain tolerance and vital signs alteration on pra and post operative, before and after intervention to pain tolerance, p = 0.000. Before intervention sistole (X=115.67) and diastole (X=76.33), after intervention sistole (X=115.00) and diastole (X=75.33), before and after intervention to blood pressure, sistole and diastole are p= 0.004 and p = 0.026, respectively. Before intervention (X=17.60), after intervention (X=17.40), before and after intervention to respiration, p = 0.021. Before intervention (X=84.80), after intervention (X=83.73), before and after intervention to pulse rate, p = 0.043. The result showed that there are significant correlation between deep breathing learning effect to pain tolerance and vital signs alteration.